The French Government and Spain : summary of speech by Jean Longuet - Longuet, Jean
015b_0043_001 THE FRENCH GOVERNMENT AND SPAIN Meeting of the National Council of the French Socialist Party, November 8, 1936. Le Populaire, November 9, 1936. Extract from Speech by Jean Longuet " ..... Speaking later on the events in Spain, Longuet declared that if the policy of non-intervention was perhaps necessary, it was, after all, only the policy of the lesser evil. He recalled in this connection that the French Government took the initiative in the policy of non-intervention in consideration of the attitude of the British Government. It (the British Government) had taken the precaution of saying that it would not be at the side of France if France intervened in Spanish affairs ....." sent by W. Gillies 292/946/15b/43